2020
DOI: 10.20473/bhsj.v3i1.19129
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglicemic and Antioxidant Activity of Petiveria alliacea in Diabetic Rat Models

Abstract: Introduction: Diabetes mellitus is a degenerative disease characterized by chronic hyperglycemia conditions in the body. Various complications of diabetes mellitus are caused by oxidative stress condition. Petiveria alliacea (P. alliacea) is a potential plant and easy to grow in hot regions. Leaf extracts of P. alliacea contain flavonoids and tannins which work as antidiabetic and antioxidant. In addition, other compounds found in P. alliacea leaf extracts like linoleic acid and allantoin show an increase in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…As previously described, hyperglycemia causes oxidative stress and inflammation [27][28][29][30] and induces mitochondria and endoplasmic reticulum to produce free radicals, reactive oxygen species (ROS), and reactive nitrogen species. Oxidative stress occurs due to an imbalance between a large number of free radicals and the inability of endogenous antioxidants, such as glutathione peroxidase, catalase, and superoxide dismutase.…”
Section: Discussionmentioning
confidence: 94%
“…As previously described, hyperglycemia causes oxidative stress and inflammation [27][28][29][30] and induces mitochondria and endoplasmic reticulum to produce free radicals, reactive oxygen species (ROS), and reactive nitrogen species. Oxidative stress occurs due to an imbalance between a large number of free radicals and the inability of endogenous antioxidants, such as glutathione peroxidase, catalase, and superoxide dismutase.…”
Section: Discussionmentioning
confidence: 94%
“…Mustika et al [18]. showed that the extract of P. alliacea leaves decreased the blood glucose level in the T2DM mouse model and increased the 5′-adenosine monophosphate-activated protein kinase (AMPK) expression in the liver [16]. These studies provide hope that P. alliacea may be used to control the inflammation in hyperglycemic conditions, thereby reducing IR.…”
Section: Introductionmentioning
confidence: 94%
“…Petiveria alliacea is a perennial plant widely found in Indonesia and empirically used as a folk medicine to treat various diseases, such as diabetes, bleeding cough, anti-inflammation, and immunomodulatory. Several studies revealed that P. alliacea has anti-inflammatory [12][13][14][15] and antioxidant activities [16]. All parts of P. alliacea are available for use in treatment from oxidative damage of cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…After STZ injection into experimental animals, there is a risk of sudden hypoglycemia. To prevent this, experimental animals are given a 10% dextrose solution for several days after injection [10,11]. STZ injection can have an impact, resulting in either type 1 or type 2 diabetes, depending on the age and dose of STZ injected [9].…”
Section: Streptozotocinmentioning
confidence: 99%
“…Diabetes mellitus animal models can be obtained using Wistar rats (Rattus norvegicus) injected with intraperitoneal streptozotocin (STZ) at a dose of 50 mg/kg body weight. It is known that within 2 days after injection, rats experience hyperglycemia, measured after a 6-hour fast [11].…”
Section: Streptozotocinmentioning
confidence: 99%